Identificação, caracterização e controle de Globisporangium spp. e Pythium spp. isolados de plântulas de soja no sul do Brasil - Molin, Cleisla (2022)
Soybean damping-off is a common problem in several fields in southern Brazil. However, there is limited information about which species of Globisporangium and Pythium species can be found causing damping-off as well as control methods that are most effective in managing the disease. Thus, the objectives of this study were i) to isolate, identify and determine the pathogenicity and aggressiveness of oomycetes isolated from soybean seedlings; ii) to evaluate the efficacy of chemical control through seed treatment; iii) to verify the efficacy of increasing doses of metalaxyl-M-based products; and iv) to characterize the reaction of soybean cultivars to Globisporangium spp. and Pythium spp. Initially, 33 oomycete isolates were obtained from 13 fields, and nine species were recovered: G. rostratifingens, G. irregulare, G. spinosum, G. ultimum var. sporangiiferum, P. acanthicum, P. conidiophorum, P. deliense, P. inflatum and P. torulosum. Thus, the results showed that all isolates were pathogenic to soybean, but there are differences in the levels of aggressiveness. Then, the efficiency of 15 seed treatments was evaluated (untreated control, Certeza N, Apron RFC, Maxim, Maxim XL, Maxim Quattro, Maxim Advanced, Vitavax Thiram, Standak Top, Spectro, Verango, Derosal Plus, Carbendazim, Attic and Rancona T) in two soybean cultivars (‘DM57i52 IPRO’ and ‘NEO530 IPRO’). Products containing metalaxyl-M were the most effective in controlling damping off caused by G. irregulare and G. utimum var. sporangiiferum followed by products containing thiram. Subsequently, it was evaluated whether increasing the dose of metalaxyl-M-based products could provide greater efficacy in the control of damping-off. Thus, the treatments were arranged in a factorial scheme of 3 fungicides (Apron, Maxim Advanced and Maxim Quattro) x 7 doses (0.000; 0.003; 0.006; 0.012; 0.018; 0.024; 0.030 mg of metalaxyl-M per seed) x 2 soybean cultivars (‘DM57i52 IPRO’ and ‘NEO530 IPRO’). There was a significant effect of doses in reducing the severity of root rot for both soybean cultivars. Finally, 50 soybean cultivars recommended for the M1 macroregion of southern Brazil were used to characterize their reaction to G. irregulare, G. ultimum var. sporangiiferum and P. conidiophorum. The cultivars ‘BMX Apolo’, ‘BMX Compacta’, ‘BMX Elite’, ‘BRS 5601’, ‘M5947’, ‘M6410’, ‘M6210’ were less susceptible to G. irregulare and G. ultimum var. sporangiiferum. However, the cultivars ‘BMX Ativa’, ‘BRS 543’, ‘BRS 6203’, ‘DM 5958’, ‘BMX Raio’ and ‘BMX Valente’ were less susceptible to P. conidiophorum. In conclusion, several species of Pythium and Globisporangium can be found in soybean fields in southern Brazil. To minimize the damage caused by soybean damping-off, different control methods should be used, such as the use of fungicides based on metalaxyl-M and thiram associated with cultivars less susceptible to the disease.